2013
DOI: 10.1590/s0103-84782013005000050
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases 2 and 9 expression in canine normal prostate and with proliferative disorders

Abstract: In this study the expression of metalloproteinases 2 (MMP-2) and 9 (MMP-9) in canine normal prostates and with proliferative disorders was evaluated to verify the role of these enzymes in extracellular matrix remodeling (ECM) and in the tissue invasion process. A total of 355 prostatic samples were obtained, from which 36 (10.1%) were normal prostates, 46 (13.0%) with benign prostatic hyperplasia (BPH), 128 (36.1%) with proliferative inflammatory atrophy (PIA), 74 (20.8%) with prostatic intraepithelial neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(37 reference statements)
0
9
0
1
Order By: Relevance
“…In canine PC, MMP-2 and MMP-9 were previously evaluated and the authors found overexpression when compared PC to normal prostate. However, the authors did not compare the results with collagen expression [40], as well as we did not measure MMPs in the present study. Based on this previous description in canine PC [39], MMP-2 and 9 overexpression can induce collagen degradation interfering in the collagen evaluation by IHC and PSR.…”
Section: Discussionmentioning
confidence: 85%
“…In canine PC, MMP-2 and MMP-9 were previously evaluated and the authors found overexpression when compared PC to normal prostate. However, the authors did not compare the results with collagen expression [40], as well as we did not measure MMPs in the present study. Based on this previous description in canine PC [39], MMP-2 and 9 overexpression can induce collagen degradation interfering in the collagen evaluation by IHC and PSR.…”
Section: Discussionmentioning
confidence: 85%
“…These authors suggest that collagen reduction in PC could be the result from high metalloproteinase activity. In a study from Faleiro et al [26] in canine PC, MMP-2 and MMP-9 were overexpressed, when compared to normal prostate, but the authors did not compare the results with collagen expression.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed using a procedure modified from a previously described protocol using an automated staining system (BenchMark XT; Ventana Medical Systems, Inc., Tucson, AZ, USA) and an alkaline phosphatase detection method (Enhanced Alkaline Phosphatase Detection Red Kit; Ventana) 16. Epitope retrieval was performed with Cell Conditioning 1 Solution (Ventana) at 96°C for 90 minutes, followed by rinsing in reaction buffer (Ventana).…”
Section: Methodsmentioning
confidence: 99%